Implementasi Kewenangan DKPP Pasca Putusan Mahkamah Konstitusi Nomor 115/PHPU.D-XI/2013 - Darwis, Muh. Salman (Jurnal Konstitusi, 2015)
The existence of DKPP as one of the administration institutions of elections, causing a variety of problems in the implementation of its authority. This is due to the absence of a sufficiently clear parameters or benchmarks used by DKPP in dealing with the violations of code of conducting for the election. Finally, using the argument of the restorative justice, DKPP takes care ofthe implementation of the election by assigning the couplecandidate of participants forthe election and solves the disputes of determination of couple candidate for the election. The decison of Constitutional Court No. 115/PHPU.D-XI/2013,warns the DKPP to be consisten,adjudicating, and determine the violations of code of conduct in theimplementation of the election. Besides, decisions of DKPP shouldcharacteristically be recommendation and not be final and binding because it inflicts psychological effects forboard of KPU as well as bawaslu that is thefear of dismissal sanction or temporary dismissal and potentially incurring prolongedlaw polemic.